2020
DOI: 10.3390/f11070740
|View full text |Cite
|
Sign up to set email alerts
|

Surface Canopy Position Determines the Photosystem II Photochemistry in Invasive and Native Prosopis Congeners at Sharjah Desert, UAE

Abstract: Plants have evolved photoprotective mechanisms in order to counteract the damaging effects of excess light in hyper-arid desert environments. We evaluated the impact of surface canopy positions on the photosynthetic adjustments and chlorophyll fluorescence attributes (photosystem II photochemistry, quantum yield, fluorescence quenching, and photon energy dissipation), leaf biomass and nutrient content of sun-exposed leaves at the south east (SE canopy position) and shaded-leaves at the north west (NW c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 81 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Also, P. juliflora has several adaptive features that enable it to grow well and even flourish in very poor dry hot desert habitats that are commonly considered to be unsuitable for the dominance of many other plant species [ 11 , 12 , 13 , 74 ] For example, the deep taproot of this species allows it to secure its water requirements during dry seasons and hence to invade the dry arid lands [ 74 ]. In addition, P. juliflora was able to tolerate high sun intensity and temperatures of the hyper-arid environment of the Gulf region by avoiding permanent damage of the photosynthetic apparatus that happened by lowering PSII efficiency and dissipating extra light energy through the increase of non-photochemical quenching [ 12 ]. Furthermore, the intrinsic water-use efficiency of P. juliflora was significantly greater than in the congeneric native P. cineraria in the arid deserts [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, P. juliflora has several adaptive features that enable it to grow well and even flourish in very poor dry hot desert habitats that are commonly considered to be unsuitable for the dominance of many other plant species [ 11 , 12 , 13 , 74 ] For example, the deep taproot of this species allows it to secure its water requirements during dry seasons and hence to invade the dry arid lands [ 74 ]. In addition, P. juliflora was able to tolerate high sun intensity and temperatures of the hyper-arid environment of the Gulf region by avoiding permanent damage of the photosynthetic apparatus that happened by lowering PSII efficiency and dissipating extra light energy through the increase of non-photochemical quenching [ 12 ]. Furthermore, the intrinsic water-use efficiency of P. juliflora was significantly greater than in the congeneric native P. cineraria in the arid deserts [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a change in soil texture would exacerbate the invasion rate of P. juliflora in such arid deserts. Moreover, P. juliflora gains more advantages over its native competitors, making it spread faster in the infested countries [ 12 , 13 ]. The investigations conducted in the Sultanate of Oman, one of the top threatened countries in the desert biome according to our models, indicated that P. juliflora germinated faster and greater, even under stress conditions, such as heat and drought, as compared with its native congener P. cineraria [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors indicated that it is extremely difficult to separate the growth and physiological secondary effects afrom the primary impacts caused by allelochemicals. However, the secondary impacts led to the disruption of cell differentiation, plant water status, water uptake, respiration, signal transduction, photosynthesis and enzyme function [ 3 , 6 , 7 , 10 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll fluorescence quenching and non-photochemical quenching were calculated as demonstrated by Kramer et al [ 24 ], and Bilger et al [ 25 ]. The excess photon energy of the PSII reaction center was calculated as (1−qP)/NPQ [ 18 , 22 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%